Revisión crítica del concepto "psicosomático" a la luz del dualismo mente-cuerpo - Lemos Hoyos, Mariantonia (2022)
The concept “psychosomatic” brings with it a heavy semantic burden that has its roots in the philosophical dualism, accentuated in the Cartesian proposal, which has spread through modern rationality and with it the conception of the disease, in the medical field as well as in psychology. The following article provides a brief discussion of this concept, outlining the main perspectives in addressing the mind-body connection. In conclusion, it is necessary to review dualistic positions and the addition of a new view of notions about health and illness, from which psychosomatic concept becomes redundant.